Implementasi Akuntansi Zakat pada Laporan Keuangan Lembaga Amil Zakat di Indonesia - Resa Ajeng Setianingrum; Mardiana Mardiana (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
This study aims to examine the implementation of zakat accounting in the financial reports of zakat management institutions in Indonesia, with a focus on compliance with PSAK 109. A qualitative-descriptive method was employed through a case study approach. Data were obtained from financial records, interviews, and documentation at LAZ XYZ. The findings reveal partial compliance with PSAK 109, especially in the categorization and presentation of zakat and non-zakat funds. Challenges include limited technical resources and understanding of sharia-based financial reporting. Strategic improvements are recommended to enhance accountability and public trust in zakat management.